The flame bearer [compact disc, unabridged] : a novel - Cornwell, Bernard (Cornwell, Bernard. Last kingdom, 2016)
Britain is in a state of uneasy peace. Northumbria's Viking ruler, Sigtryggr, and Mercia's Saxon Queen Aethelflaed have agreed a truce. And so England's greatest warrior, Uhtred of Bebbanburg, at last has the chance to take back the home his traitorous uncle stole from him so many years ago, and which his scheming cousin still occupies.